Study on the optimun cutting conditions for turning operations - 211766 Zulkefle Mohamad (1991)
A theoretical investigation is carried out to establish a procedure for calculating the optimum cutting condition with maximum production rate as the objective functions for a given cutting tool and workpiece combination. The optimization method is described in details for roughing and finishing operations. Some constraints which effect the optimum cutting conditions are elaborated, such as, allowable tool force, power available, component instability, workholding limitation, cutting tool velocities, surface finish and workpiece accuracy. A computer software is developed to assist in the calculation using WATFOR 77 language. The search for the optimum is using grid point search technique where the point is calculated using numerical method. The point obtained is tested in the first instance, to see if it violates any one of the velocity independent constraint. Otherwise, the optimum cutting velocity is calculated using the general tool life equation. If more than one pass is necessary to rough machine a given area, the optimum depth of cut are altered. Seven different cases of doing this are discussed. To demonstrate the system, the cutting conditions for machining a simple component are presented.